The Effectiveness of Nutrition Education Using Instagram on Body Image Perception and Eating Patterns of Adolescents with Overweight Incidence at SMPN 4 Samarinda - Triana, Andini Chantika; Anshory, Jamil; Saputri G., Riska Mayang (Universitas Pendidikan Indonesia, 2023)
Background : Overweight is a widespread issue among children and adolescents aged 5-19 in multiple countries. Adolescents are influenced by physical activity and social media, affecting body image perception and health, potentially leading to low self-esteem, depression, disrupted physical activity, and eating patterns. This study aims to determine the effectiveness of nutrition education using Instagram on body image perception and eating patterns of adolescents with overweight incidents at SMP Negeri 4 Samarinda.Research Methods : Quantitative quasi-experimental research with the One-Group Pretest-Posttest research design. The research subjects were 16 students who were taken using a purposive sampling technique with the Lemeshow formula in February-March 2023 at SMPN 4 Samarinda. Body image perception uses the BSQ-34 questionnaire. Dietary patterns were obtained using the SQ-FFQ. Data were analyzed using the Wilcoxon test.Research Result : The results of this study indicate that there is effectiveness of nutrition education using Instagram on body image perception and the pattern of adolescents with overweight incidents at SMPN 4 Samarinda is indicated by a p-value (0.05). However, there is no effectiveness of nutrition education using Instagram on eating patterns (fat intake) indicated by a p-value ( 0.05).Conclusion : There is a significant relationship between nutrition education using Instagram on body image perception and eating patterns of adolescents and the incidence of overweight at SMPN 4 Samarinda. There is no significant relationship between diet (fat intake) and the incidence of adolescent overweight at SMPN 4 Samarinda